2022
DOI: 10.1007/s10865-022-00302-9
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and tolerance of uncertainty: relationship to trust in COVID-19 health information and vaccine hesitancy

Abstract: The COVID-19 crisis has exposed the public to considerable scientific uncertainty, which may promote vaccine hesitancy among individuals with lower tolerance of uncertainty. In a national sample of US adults in May–June 2020, we examined how both perceptions of uncertainty about COVID-19 and trait-level differences in tolerance of uncertainty arising from various sources (risk, ambiguity, and complexity) are related to vaccine hesitancy-related outcomes, including trust in COVID-19 information, COVID-19 vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 40 publications
3
17
2
Order By: Relevance
“…However, as IU is indeed a significant predictor of the majority of our measures, this implies that IU could predict vaccination decisions (i.e., getting vaccinated, having children vaccinated, and recommending the vaccine), regardless of the level of uncertainty perceived in the situation. This is in line with the results of Gillman et al [ 4 ] who concluded in their study, “We found that individual trait-level differences in tolerance of uncertainty were associated with vaccine hesitancy”. A similar pattern was found for attitudes towards vaccination which predicted vaccination decisions, whereas our ANOVAs showed little evidence of differences based on the perceived level of uncertainty (except for recommendations and vaccinating one’s children if one had any).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…However, as IU is indeed a significant predictor of the majority of our measures, this implies that IU could predict vaccination decisions (i.e., getting vaccinated, having children vaccinated, and recommending the vaccine), regardless of the level of uncertainty perceived in the situation. This is in line with the results of Gillman et al [ 4 ] who concluded in their study, “We found that individual trait-level differences in tolerance of uncertainty were associated with vaccine hesitancy”. A similar pattern was found for attitudes towards vaccination which predicted vaccination decisions, whereas our ANOVAs showed little evidence of differences based on the perceived level of uncertainty (except for recommendations and vaccinating one’s children if one had any).…”
Section: Discussionsupporting
confidence: 92%
“…The results of this exploratory mediation make sense if we consider IU as a construct closely related to stress and anxiety (i.e., this construct was originally studied in the context of anxiety disorders and has shown strong links with anxiety in studies about the perceived viral threat during a pandemic; [ 10 , 38 ]) and that stress can lead to favorable attitudes towards vaccination [ 39 ]. In addition, a recent study showed that IU was associated with more threat perception and pandemic-related stress, which were associated with more pandemic-related anxiety [ 4 ]. The links between IU and confidence in one’s judgment were also previously studied by Jensen et al [ 29 ] who showed that a high level of IU can be associated with decreasing confidence in decisions across several blocks of decision-making, while a low level of IU is associated with increasing confidence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations